2006
DOI: 10.1002/jcop.20097
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of mental health consumer/survivor initiatives: Part 1—Literature review and overview of the study

Abstract: Mental health consumer-run organizations are alternatives to mainstream

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Those with serious mental illness universally indicate that they believe peer support is one of the most helpful interventions they have experienced. Several studies have confirmed these perceptions [113][114]. Peer support groups are run by individuals with serious mental illness for others who have similar problems.…”
Section: Peer Supportmentioning
confidence: 93%
“…Those with serious mental illness universally indicate that they believe peer support is one of the most helpful interventions they have experienced. Several studies have confirmed these perceptions [113][114]. Peer support groups are run by individuals with serious mental illness for others who have similar problems.…”
Section: Peer Supportmentioning
confidence: 93%
“…Included texts originate in many different disciplines, reflecting a lack of disciplinary dominance over this field of research. However, a number of authors are represented in several texts, which is especially noteworthy with regard to Nelson who is the co-author of six texts Nelson et al 2006aNelson et al , b, 2007Nelson et al , 2008Nelson and Lomotey 2006) and Brown who is represented as author or co-author of eight texts (Brown 2009a, b;Brown et al 2007aBrown et al , b, 2008aBrown et al , b, 2010Brown and Townley 2015). The frequent representation of US authors from community psychiatry studies potentially creates bias to issues central within that context and field.…”
Section: Categorization and The Synthesizing Processmentioning
confidence: 99%
“…MHSUOs aim to be different from traditional mental health services, often understood to be bureaucratic and oppressive (Nelson et al 2006a). Alternative organizational forms have been developed in MHSUOs, involving high levels of volunteers, processes for democratic decision making and service user-exclusive groups (Boyce et al 2010;Kleintjes et al 2013b;Tanenbaum 2012).…”
Section: Processes Of Organizational Professionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Social support/functioning Individuals involved in peer-run services had improved social functioning compared with individuals in traditional mental health services. 28 People continuously involved in peer support programmes over three years scored significantly higher than comparison groups on a measure of 'community integration'. 29 Participants who received peer support demonstrated improved social support, enhanced social skills and better social functioning.…”
Section: Economic or Monetary Impactmentioning
confidence: 99%